Spiritual ascent in Buddhism, Christianity and Islam: a study in comparative mysticism - Solihu, Abdul Kabir Hussain (London Academy of Iranian Studies, 2007)
This study examines the doctrine of spiritual ascent, central to mystical experience, as taught in theistic mysticism, as exemplified in Christianity and Islam, and non-theistic or monistic mysticism, as manifested in Buddhism. The study highlights the common characteristics and the variations in the teachings of spiritual ascent according to these three world religions. The primary objective is to explore how the universal human aspiration for a transcendent al experience common to these mystical traditions could be brought into contact with, or understood in the light of, the belief systems and values in which a particular mystical concept or formula sprouts.